Diagnostic accuracy of strain ultrasound elastography in differentiating benign and malignant thyroid nodules, taking histopathology as gold standard - Fatima, Maham; Younus, Shifa; Maqsood, Hamza; Younas, Amna; Mukhtar, Farah; Shah, Mahnoor Fatima; Raza, Hassan; Mazhar, Saim; Qasim, Muhammad; Khakwani, Muhammad Shahzeb Khan (International Journal of Research in Medical Sciences, 2021)
Background: Elastography is a method recently being used in the evaluation of thyroid nodules by comparing tissue elasticity. Strain and shear wave elastography are two types of elastography still being used in clinical practice. Two kinds of elasticity can be assessed by strain elastography. First, colors around and within the nodules are evaluated and visually scored according to the 4-5 scale scoring systems. The aim of this study was to determine the diagnostic accuracy of strain ultrasound elastography in differentiation between benign and malignant thyroid nodules, taking histopathology as gold standard Methods: Total of 101 patients with palpable thyroid nodule of any size of age 30-70 years of either gender were included. Patients with previous thyroid surgery and already proven histopathology were excluded. Strain ultrasound elastography was performed in every patient by using a highresolution unit with a linear array probe centred at 7.5 MHz. Strain ultrasound elastography was performed in every patient by a consultant radiologist in the presence of researcher and benign or malignant thyroid nodules was noted. Strain USG elastography findings were compared with histopathology report. Results: All the patients were subjected to strain ultrasound elastography. USG supported the diagnosis of malignant thyroid nodules in all 52 patients. Histopathology confirmed malignant thyroid nodules in 47 (true positive) cases where as 5 (false positive) had no malignant lesion on histopathology. In USG negative patients, 46 were true negative while 3 were false negative. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of strain ultrasound elastography in differentiation between benign and malignant thyroid nodules, taking histopathology as gold standard is 94.0%, 90.20%, 90.38%, 93.88% and 92.08% respectively. Conclusions: According to this study, strain ultrasound elastography is the non-invasive modality of choice with high diagnostic accuracy in diagnosing malignant thyroid nodules.